Quantifying the cost of nutritious diets and dietary impacts on health: Economic approaches to global food systems and nutrition transition - Bai, Yan. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Food and Nutrition Policy and Programs.; Advisor: William Masters.; Committee: Elena Naumova, and Gitanjali Singh.; Keywords: Nutrition, and Economics.; The cost of nutritious diets that would improve health outcomes has become a major concern for governments and development agencies involved in food systems around the world. This dissertation uses observed food prices to measure the affordability of healthy diets globally and in East Africa, and uses observed quantities consumed to measure the quality of actual diets in terms of health outcomes in the United States. These studies combine market data with nutritional information on food composition and its consequences for human health, using economic principles to construct and apply metrics that can guide policies and programs with transparent methodologies and robust validation. Applying multiple datasets and quantitative methods, we examined two novel indices developed using economic approaches. The Cost of Nutrient Adequacy (CoNA), rooted in the cost-of-living indices, quantifies the least cost of a diet meeting daily nutritional needs, and it is proposed as a measure of access to nutritious diets for low- income populations. Using a global food price dataset of the World Bank, Study 1 assessed CoNA over 20 demographic groups in 172 countries in 2017. Study 2 further measured the seasonality of CoNA in Tanzania, Malawi, and Ethiopia, using time-series subnational price datasets. Study 3 investigated the second index, the International Diet-Health Index (IDHI), inspired by weights in economic indices, measuring the dietary impacts on health given a population's health status and disease burdens. Using data from the National Health and Nutrition Examination Survey (NHANES), we analyzed the trends of IDHI in the US from 2003-2014 and compared IDHI with a modified Alternative Healthy Eating Index (mAHEI), as well as validated indices against all-cause mortality. Study 1 finds that CoNA, with a global median of $2.30 (IQR: 1.95-2.75) in 2017, peaked for males and lactating women of 14-18 y/o. Female groups of all ages faced higher costs per 1,000kcal compared to their male peers. Study 2 finds the significant intensity of seasonality in CoNA in Malawi, Tanzania, and Ethiopia (10.0 vs. 6.3 and 4.0%), driven primarily by synchronized price rises for nutrient-dense foods, especially fruits and vegetables. Seasonality in CoNA also presents regional variations within countries. Study 3 reveals that the adjusted-mean of IDHI in the US declined from -0.314 in 2003/04 to - 0.325 in 2013/14. Non-Hispanic Black Americans had persistently lower IDHI, and disparities in IDHI widened over time by levels of income, and education. IDHI was more closely correlated with the mAHEI at higher levels of diet quality, and both indices were strongly associated with total mortality. Nutritious diets are not affordable for the global poor, and the costs differ across demographic groups and over seasons. CoNA could be used as a metric to target populations at risk of undernutrition and to evaluate the nutritional performance of food systems over localities and time. Similarly, IDHI is a valid tool for measuring diet-related health impacts in the context of a population's most prevalent diseases, potentially offering tailored guidance regarding how best to reduce diet-related health disparities. International collaboration on nutrition-sensitive data is urgently needed in global applications of both indices.